2015
DOI: 10.3109/13685538.2015.1034686
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D is significantly associated with total testosterone and sex hormone-binding globulin in Malaysian men

Abstract: 25(OH)D is significantly associated with total testosterone and SHBG in Malaysian men but this association is BMI-dependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
3
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 35 publications
1
38
3
1
Order By: Relevance
“…differences in sun exposure, diet and BMI between sexes). 52,55 Indeed, 25-(OH)D has been significantly and positively associated with total testosterone and SHBG levels before and after adjustment for age and ethnicity, 56 although VitD supplementation per se does not appear to influence testosterone levels. 57 In addition, short-term administration of testosterone does not appear to alter 25-(OH)D levels.…”
Section: Discussionmentioning
confidence: 99%
“…differences in sun exposure, diet and BMI between sexes). 52,55 Indeed, 25-(OH)D has been significantly and positively associated with total testosterone and SHBG levels before and after adjustment for age and ethnicity, 56 although VitD supplementation per se does not appear to influence testosterone levels. 57 In addition, short-term administration of testosterone does not appear to alter 25-(OH)D levels.…”
Section: Discussionmentioning
confidence: 99%
“…In men, 25(OH)D levels are positively related to T levels,[914] and this association varies by vitamin D receptor genotype[15] and may be attenuated after accounting for adiposity. [9] Treatment with vitamin D supplements may increase T levels.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Treatment with vitamin D supplements may increase T levels. [16] Data from testicular cell cultures suggest that vitamin D, especially 1,25-dihydroxyvitamin D3, has a major role in male steroidogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…[21] VD was significantly and positively associated with T levels before and after adjustment for age and ethnicity. [19] Vitamin D (actually is a potent steroid hormone) which is positively correlated with T, exhibits a concordant seasonal fluctuation [38] , and elevates when T is supplemented in androgen deficient men. [28] Amazingly, the reverse situation is also true, suggesting that VD supplementation might increase T levels.…”
Section: Vitamin D and Endocrine Systemmentioning
confidence: 99%
“…In an animal study on diabetic rats, it was demonstrated that treatment with VD for 12 weeks increased the serum level of T in treatment groups. [26] In a clini- Abnormalities in calcium and phosphorus homeostasis [10,15] Bronchial asthma [4,7] Coronary artery disease [14,16] Erectile dysfunction [9,17,18] Heart failure [10,16] Hypertension [9,14] Hypogonadism [19][20][21][22] Impaired vascular endothelial and smooth muscle function [9,16] Increased immune or inflammatory response [23,24] Infertility [25,26] Metabolic syndrome [10,14,27] Osteoporosis [19,28,29] Peripheral vascular disease [15,30] Respiratory diseases [3,4] Wearing sunscreen clothes cal randomized controlled trial, which is the first on this topic in literature, Pilz et al [39] investigated the effect of VD supplementation on androgens in men. The results were significant and the researchers observed that overweight men with VDD had a clinically meaningful increase in serum T levels after VD supplementation for 1 year.…”
Section: Vitamin D and Endocrine Systemmentioning
confidence: 99%